Progress, critical challenges, and translational prospects of intranasal administration of botanical essential oils for the treatment of depression - Cheng, Kexin; Zhao, Hongyi; He, Kui; Xia, Xiuwen; Wang, Yi; Wang, Shuyu; Li, Weihong (Frontiers in Pharmacology, 2026)
Depression is a highly prevalent and disabling psychiatric disorder worldwide. However, currently available first-line antidepressant therapies are frequently limited by delayed onset of action, a high incidence of adverse effects, and inconsistent therapeutic efficacy, underscoring the urgent need for alternative treatment strategies. Botanical essential oils are rich in volatile, lipophilic small-molecule metabolites and are characterised by multi-metabolite, multi-target synergistic regulatory properties. When combined with intranasal administration, these metabolites can exploit the nose-to-brain pathway to bypass the blood–brain barrier and achieve rapid central nervous system delivery, thereby emerging as a promising research focus in antidepressant therapy. In this study, a systematic review was conducted in strict accordance with the PRISMA guidelines, encompassing 40 relevant studies published between 2015 and 2025. We comprehensively summarised intranasal administration paradigms of botanical essential oils, including dosing regimens and temporal patterns, elucidated their core antidepressant mechanisms, and placed particular emphasis on their rapid modulatory effects on olfactory neural circuits and emotion-related brain regions. In addition, recent advances in novel delivery technologies—such as nanoemulsions, lipid-based nanocarriers, and mucoadhesive delivery systems—were critically reviewed for their roles in enhancing brain-targeting efficiency and formulation stability. Meanwhile, this review objectively evaluates major limitations in the current body of research, including insufficient experimental rigour, inconsistent administration parameters and quality control, inadequate systematic toxicological assessment, and substantial challenges associated with the standardisation of essential oil compositions. By integrating available experimental evidence with network pharmacology analyses, this work aims to provide a theoretical foundation and strategic guidance for future mechanistic studies, formulation optimisation, and the clinical translation of intranasal botanical essential oil–based interventions for depression.